Diazepam enhances melanogenesis, melanocyte dendricity and melanosome transport via the PBR/cAMP/PKA pathway. (November 2019) - Lv, Jinpeng; Fu, Ying; Gao, Rongyin; Li, Jiawen; Kang, Maofan; Song, Guoqiang; Yun, Changjun
Abstract: Diazepam is a medicament of the benzodiazepine family and it typically produces a sedative effect. Researchers have revealed that diazepam can induce melanogenesis and produce dendrite-like structures in B16 melanoma cells. However, the associated mechanisms of melanogenesis and phenotypic alterations have mostly remained unknown. In this study, we determined the effects of diazepam on melanogenesis, cellular phenotypic alterations, the location of melanosomes and the expression of relevant proteins in melanocytes using Masson–Fontana ammoniacal silver staining, scanning electron microscopy, immunocytochemistry and western blot analysis. Our results collectively indicated that diazepam had a pivotal role in melanocytes by enhancing melanin synthesis, melanocyte dendricity, melanosome trafficking, and capture at the dendrite tips. These functions might be attributed to the fact that diazepam activated the peripheral benzodiazepine receptor (PBR). This increased intracellular levels of cAMP, which stimulated the phosphorylation of cAMP response element-binding (CREB). As a result, this increased the tyrosinase, microphthalmia-associated transcription factor (MITF), Rab27a, Myosin Va, Rab17 and Cdc42 expression. This caused melanogenesis and melanosome transport. Therefore, our findings may provide a potential strategy for treating anti-hypopigmentation disorders.